Clear Thinking : Turning Ordinary Moments into Extraordinary Results - Parrish, Shane (New York, Penguin Random House, 2023)
"A must-have manual for optimizing decision-making, gaining competitive advantage, and living a more intentional life"--
Keywords: Decision making